Uncovering discordance between taxonomy and evolutionary history in Florida raccoons. Issue 1 (2nd January 2017) - Trujillo, Alexa L.; Hoffman, Eric A.
Abstract : Due to perceived isolation of near shore islands, there are currently five subspecies of raccoons ( Procyon lotor ) recognized in Florida, USA. In this study, we elucidated molecular genetic differences between subspecies using 173 samples from eight localities collected throughout Florida. We sequenced two mitochondrial genes and genotyped eight nuclear microsatellite loci to test two hypotheses: (1) the five morphologically and geographically defined subspecies of raccoons in Florida represent genetically distinct populations and (2) due to differing habitat availability between island and mainland subspecies, island populations would exhibit reduced levels of genetic diversity compared with mainland populations. Our mitochondrial results identified 37 unique haplotypes, many of which are shared between described subspecies. However, our analyses of genetic differentiation suggest a recent restriction of gene flow among three clusters of raccoons, which do not correlate to traditional geographies for subspecies identification. Finally, we provide evidence of reduced genetic diversity in island populations compared with their mainland counterparts using both mitochondrial and microsatellite data, which demonstrate that haplotype diversity, allelic richness, and heterozygosity are significantly reduced in island sites. These data stress the importance of using multiple lines of evidence when naming taxa to ensure concordance between evolutionary history and taxonomy.